Ensaios empíricos sobre diferenciais salariais por sexo no Brasil - Rodrigues, Fábio Lúcio (2020)
This thesis is composed of two essays in microeconomic that bring empirical applications on wage composition and income differentials by sex in Brazil. The first essay seeks to identify representative variables for social capital at the level of the individual and verifying its effects on the composition of wages and the consequent wage difference by sex and incomes quantiles. The PNS 2013 was used to execute different econometric strategies to detect the impact of social capital on wages per sex. The results point to a clear effect of the social capital stock on wages in general, but with a greater impact on women's wage premiums both on the average and on the earnings of women who are in the lowest salary rangers. The second essay consists of verifying the effects of occupations in prestigious professions on the composition of wages by sex, as well as the magnitude of the wage premium generated by occupational segregation along the income distribution. For this purpose, the 2019 PNADC was used to classify occupational segments by predominance of sex, in addition to identifying workers who occupy professions considered to be of social prestige and to estimate quantiles models by recentered influence functions to capture the effects of professional choice by profession of prestigious and the occupational segregation on wage composition. The results indicate that, despite the unequivocal occupational segregation against women, there is an evident wage advantage in occupying prestigious professions in Brazil and that the female labor force can partially compensate the existing wage gap in the structure of labor relations when you choose these occupations.